Design and fabricate test rig structure for an automotive turbocharger testing apparatus - Daelami, Aminuddin (2008)
This project focuses in design and fabricates the main structure for turbocharger testing apparatus. To achieve the project objective, the test rig structure must be design and suitable for place the turbocharger testing apparatus. The test rig structure should be fabricated using welding process and some laboratory skills. This project flow must start from study, design, and lastly fabrication process. Before fabricate the test rig structure, a study has been made for the design by searching information from the internets, reference books and journal magazines. It is important to study about the test rig structure because, to get the basic information about the test rig structure design. The fabrication process for this project must through a lot of process that must be followed step by step. This is to ensure that the design that has been fabricated followed the design specification. These test rig structure will combine with the turbocharger testing apparatus that has been fabricate by other final year student. The turbocharger testing apparatus consists of turbocharger itself, variable speed pump and piping system. The variable speed pump is the power source to working the turbocharger testing apparatus. The test rig structure is available for any addition in the future. The structure was design to have the extra space for any application addition such as computer that can analysis and produce data for the air flow in the turbocharger testing apparatus.